The paradox of secrecy in African traditional religion - Kanu, Ikechukwu Anthony (Journal of religion and human relations, 2018)
Recent studies in the area of religion, especially in the last twenty years, have led to the resurgence of interest in the issue of secrecy in religions. This has emerged as scholars from different openings of knowledge have sought entrance into different religious treasures of secret knowledge, the limitation of knowledge to the divine, secret religious activities and various other secret religious traditions. Theorists of religion, anthropologists, sociologists, psychologists, philosophers, etc., have shown in their studies that secrecy is an important element in most religious traditions and specific religious practices. In the area of African Traditional Religion (ATR), secrecy constitutes a fundamental problem. Many African priests, priestesses and other sacred functionaries, who are the custodians of this ancestral religious heritage, are not always willing to disclose major aspects of ATR. Medicine-men or practitioners of African medicine hardly reveal the elements necessary for any effective medicine to an investigator. The result is that many of them die with their knowledge, without transmitting it to the world or the next generation. In a world that is constantly and speedily globalizing, this work argues that African Traditional Religion needs to open up itself for the preservation of the religion both as a practice and an area for research. For the purpose of this research, the hermeneutic and phenomenological methods of inquiry were employed.Keywords: Secrecy, African, Traditional, Religion, Medical